Optimalisasi Potensi Wisata Desa Serangan Melalui Pendekatan Berkelanjutan: Studi Kasus Menggunakan Metode TOWS, EFAS, dan IFAS - Yusni Wiarti, Luh; Kusuma Dewi, Sheely; Bagus Gede Agung Widana, Ida; Ayu Nyoman Aridayanti, Dewa (Journal of Comprehensive Science, 2024)
Serangan Village in Denpasar, Bali, is recognized as an innovative tourist destination, having won the 2023 Anugerah Desa Wisata award. This recognition is supported by a variety of attractions such as Pura Sakenan, Asyuhada Mosque, Melasti Beach, mangrove forests, the Turtle Conservation and Education Center (TCEC), local traditions, and unique culinary offerings. This study aims to identify the internal (strengths and weaknesses) and external (opportunities and threats) factors affecting Serangan Village and to formulate strategies for sustainable tourism development based on the four main pillars of sustainable tourism destination criteria according to Minister of Tourism Regulation No.9 of 2021. A qualitative descriptive method using TOWS analysis, EFAS, and IFAS matrices was employed, with data collected through observation, interviews, and documentation. The results indicate that Serangan Village is in quadrant III, highlighting the need for effective strategies to optimize opportunities and address internal weaknesses. The strategy formulation results include leveraging the Bappenas Masterplan to build stakeholder collaboration, participating in training from the Denpasar City Tourism Office, forming a tourism impact monitoring team, implementing sustainable governance policies, utilizing social media for surveys and feedback, and developing policies for cultural asset protection and animal welfare to support sustainable tourism growth in Serangan Village.